The role of magnesium in biomaterials related infections - Luque-Agudo, Verónica; Fernández-Calderón, M. Coronada; Pacha-Olivenza, Miguel A.; Pérez-Giraldo, Ciro; Gallardo-Moreno, Amparo M.; González-Martín, M. Luisa (Colloids and surfaces, B, Biointerfaces, 2020)
[Display omitted] •Mg-based materials provide a proper antibacterial environment against nearby bacteria.•The antibacterial action of Mg is produced by a multifaceted mechanism.•pH change, ROS production, [Mg2+] and Mg nanoparticles act against bacteria.•In vivo antibacterial activity of Mg-based biomaterials remains an open question. Magnesium is currently increasing interest in the field of biomaterials. An extensive bibliography on this material in the last two decades arises from its potential for the development of biodegradable implants. In addition, many researches, motivated by this progress, have analyzed the performance of magnesium in both in vitro and in vivo assays with gram-positive and gram-negative bacteria in a very broad range of conditions. This review explores the extensive literature in recent years on magnesium in biomaterials-related infections, and discusses the mechanisms of the Mg action on bacteria, as well as the competition of Mg2+ and/or synergy with other divalent cations in this subject.